Monitoring of waterways for evidence of faecal contamination from biosolids using DNA techniques. - Pritchard, Deborah; Davies, Jill; Ho, K.; Penney, N. (Australian Water Association, 2008)
Increased nutrient levels in inland waterways have led to algal blooms and eutrophication in many agricultural regions. To ensure fertiliser inputs are managed more effectively, the source of contamination needs to be tracked and identified. Point sources could include inorganic fertilisers, livestock excreta, or more recently biosolids. The presence of faecal indicator microorganisms has been widely used to identify the presence of faeces, however, these methods cannot distinguish between human and animals samples. This study investigated PCR amplification as a molecular method to distinguish biosolids from livestock faeces of biosolids, cattle, sheep, poultry and kangaroo. This was achieved using published priming sequences and restriction site profiling of amplified DNA across the 16S rRNA gene of anaerobic gastrointestinal bacteria Bacteroides spp and Bifidobacteria spp. Preliminary investigation showed that of the three Bacteroides spp primer pairs investigated, two were useful for cow faecal material; though at lower annealing temperatures were also applicable to biosolids and sheep faecal material. The third primer pair was specific only for biosolids. All three primer pairs were unable to PCR-amplify Bacteroides spp sequences in faecal material of kangaroo. Of the three Bifidobacteria spp primer pairs, one was useful for sheep faecal material; though at lower annealing temperature was also applicable to biosolids and cow and kangaroo faecal material. The Bifidobacterium angulatum specific primer pair enabled the PCR detection of anaerobes only in biosolids and faecal material of kangaroo. The third, a Bifidobacterium catenulatum specific primer pair was suitable for faecal material of cow and at lower annealing temperatures was also applicable to the sample from sheep. Varying degrees of success were observed in faecal material from other animals. Generally, biosolids tested positive for Bacteroides and Bfidobacteria with all primers except for those specific for B. angulatum. For some primer sets, PCR amplification alone could not differentiate biosolids from other faecal samples. The serial dilution of water contaminated by a range of livestock excreta and biosolids is being examined further to enable the sensitivity of this method to be applied in the field.